Study of clinical profile of accidental poisoning in children - B., Arpitha; V., Rajanish K.; E., Adarsh (International Journal of Contemporary Pediatrics, 2020)
Background: Accidental poisoning is an important cause of morbidity and mortality in children. Poisoning is one of the medical emergencies encountered in the emergency department. Accidental poisoning is common in toddlers and pre-school children. Aim of this study was to determine the agents of poisoning and demographic distribution of children brought to Rajarajeswari Medical College and Hospital with a history of accidental poisoning. Methods: The study method was descripitive study done in pediatric department at Rajarajeswari Medical College and Hospital for 18 months, from 1 December 2017 to 31 May 2019. 25 cases were of accidental poisoning. Data was analysed by statistical analysis. Results: The prevalence of accidental poisoning was 0.1%. There was male preponderance, 16 cases were male (64%) and 9 were female (36%), hydrocarbon (40%) was the most common household agent causing poisoning, followed by pyrethroid (24%), followed by NSAID’S (8%). Most common symptom was vomiting. The mean time elapsed to reach hospital was 97.80 minutes. In majority of the cases, hospital stay was for 2 days in (13 cases (52%)). Conclusions: Children become victims of accidental poisoning. Most common agents of poisoning are household products and medications.